You've Got to Be Real: Authenticity, Performativity and Micro-Celebrity in South Africa - Dunn, Callan; Falkof, Nicky (Frontiers in Sociology, 2021)
Abstract: For many young black South African women, the competitive arena of social media offers access to significant social and cultural capital, which can be invaluable in the unequal context in which they live. In order to succeed in this high stakes environment young women carefully construct the identities and idealised selves that they present on platforms like Instagram. They display a lifestyle of glamorous consumption, showcasing exclusive brands and fashionable items and modifying and modelling themselves to fit a beauty ideal that emphasises youth, light skin, slender bodies and straight hair. As well as these physical features, young women on Instagram are also hyper-aware of the need to appear ‘authentic’: to have their online lives and selves appear natural, easy and free of artifice in order to further enhance their status as role models to other women. This article draws from an in-depth ethnographic study ofinterviews with 10 black South African ‘micro-celebrities’. It reveals the central role of authenticity in these young women’s online performances of self, and considers the contradictory impulses that require them to both ‘feel’ and ‘appear’ real. Within the framework of existing hegemonic structures, these women appear to be exercising their freedom as neoliberal citizens within a post-feminist setting. Despite the promises of freedom, however, this article reveals the way in which their performances of selfhood are powerfully constrained by normative ideas about aspiration and success.